(untitled) (Journal of Business and Technology (Dhaka), 2012)
The aim of the study is to present the current scenario of the pharmaceutical industry in Bangladesh. Since inception, there was little consensus on the development of pharmaceutical policies best suited in a developing country such as Bangladesh. Here, the pharmaceutical industry developed rapidly from the 1980s after the introduction of Drug (Control) Ordinance-1982. Adequate infrastructure and use of trained manpower were two essential requisites for implementation of national pharmaceutical policies in Bangladesh. The country was importing significant amount of medicine and also raw materials for the industry from abroad. But the industry has started to export its products in foreign market, especially in the Middle East and Europe with great success. This study tries to identify the major problems of marketing, exporting, production and operations, quality control in the pharmaceutical sector and proposes strategies to overcome these problems, it also identifies the prospects of pharmaceutical industry in Bangladesh. Keywords: Drug; Problem; Education; Health; Policy; Pharmaceutical; Deficit; Facilities; Executives. DOI: http://dx.doi.org/10.3329/jbt.v6i1.9995 Journal of Technology (Dhaka) Vol. 6(1), January-June, 2011 61-77